(untitled) (Scientific journal of the Fergana State University, 2025)
The main part of 4304.32 thousand hectares of irrigated land of our republic (about 50%) consists of soils with varying degrees of salinity, which reduces the overall productivity of agricultural crops in irrigated areas. This article provides detailed information about the irrigated soils of Bukhara district and their agrophysical properties. In addition, measures to improve soil fertility were presented.